Gallery-Supported Art Exhibitions: Critiquing “Crayola” - Choike, Anne M. (Columbia Journal of Tax Law, 2018)
This Article examines galleries’ practice of financially supporting art exhibitions presented by nonprofit art institutions, in light of the requirement imposed upon charitable organizations by the United States Internal Revenue Code to “exclusively” conduct activities that advance a public interest. Board members of nonprofit art organizations have fiduciary duties that require fidelity to the organizational mission, but courts’ deferential position results in tax rules being more restrictive in practice. Nonprofit art organizations receive federal income tax exemption conditional upon their pursuit of a charitable purpose that serves a public, rather than a private, interest. Organizations do not have a charitable, exemption-eligible purpose if they conduct their activities in a commercial manner. In addition, 501(c)(3) organizations operate subject to the condition that their assets do not benefit of any individual who exercises control over them. A further restriction on 501(c)(3) organizations, the “private benefit doctrine,” prohibits third parties to the organization from benefiting from a relationship with the nonprofit more than incidentally. It is the broader public, rather than any individual insider(s) or external private entity(s), who should benefit from the organization’s mission and activities in furtherance thereof. These rules have fairly strictly prohibited nonprofit art galleries from selling art. It is unclear whether the same rules can and do extend to the practice of gallery-supported art exhibitions, which seem to effectively enable for-profit galleries to conduct—for the price of a “donation” fee—some of their commercial activities in connection with nonprofit art exhibitions.